2000
DOI: 10.1016/s0886-3350(99)00320-x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial ingrowth in a corneal graft treated by laser in situ keratomileusis: Light and electron microscopy

Abstract: Progressive epithelial ingrowth occurred with a continuous sheet of epithelium to the flap edge. Location of epithelial ingrowth and cytokine epithelial-stromal interaction appear to be important factors in this complication. Histopathological changes in the cornea after LASIK are difficult to detect in areas with normal wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2002
2002
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…The affected lesion increased in intensity with time, suggesting that these lesions have considerable proliferating activity. Histopathological examination for such specimens in our cases was consistent with previous investigations for epithelial ingrowth after LASIK [10][11][12][13] and epithelial ingrowth after other surgeries, such as cataract extraction, keratoplasty, or penetrating trauma. 14,15 Histopathological examination in the aforementioned specimens showing normal multilayered squamous epithelium with cuboidal basal cells partly with basement membrane-like structures and flatter cells resembling wing cells or superficial cells suggest that cells in the lesion may differentiate with polarity as in the corneal epithelium.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The affected lesion increased in intensity with time, suggesting that these lesions have considerable proliferating activity. Histopathological examination for such specimens in our cases was consistent with previous investigations for epithelial ingrowth after LASIK [10][11][12][13] and epithelial ingrowth after other surgeries, such as cataract extraction, keratoplasty, or penetrating trauma. 14,15 Histopathological examination in the aforementioned specimens showing normal multilayered squamous epithelium with cuboidal basal cells partly with basement membrane-like structures and flatter cells resembling wing cells or superficial cells suggest that cells in the lesion may differentiate with polarity as in the corneal epithelium.…”
Section: Discussionsupporting
confidence: 88%
“…[10][11][12][13] In these reports, the authors succeeded in demonstrating multilayered corneal epithelial cells between the corneal flap and underlying stroma. Only one case with small old epithelial ingrowth described by Naoumidi et al that was examined 5 years after initial LASIK surgery showed homogeneous masses without any evidence of cellular materials.…”
mentioning
confidence: 99%
“…10 Some investigators believe that epithelial nests, which remain connected to the flap edge, may disappear without consequences, 11 while others believe that solitary colonies of epithelial cells are capable of transient proliferation and growth while free of peripheral connections. 12 We developed an animal model of epithelial ingrowth after LASIK and showed that implanted epithelium can survive more than 1 month without peripheral connections.…”
Section: Discussionmentioning
confidence: 99%
“…Weltweit werden pro Jahr schatzungsweise weit mehr als eine Million solcher Operationen durchgefiihrt [1,2]. Trotz aller Begeisterung fur diese refraktive Operationstechnik konnen sowohl intra-als auch postoperativ zahlreiche Komplikationen auftreten, die bis zu einer Keratoplastik fuhren konnen [3][4][5][6][7]. Histopathologische Untersuchungen nach LASIK insbesondere nach Hyperopiebehandlung wurden bisher nur aul3erst selten durchgefiihrt and zwar hauptsachlich bei Tierversuchen [8][9][10].…”
Section: Introductionunclassified